Malanville - Gaya, une dynamique de territorialisation à la frontière Benin - Niger - Edmond Sougue (Territoire en Mouvement)
This article continues the researches done by several geographers about the importance of border trade in the area between Benin and Niger. It point on the role of Malanville and Gaya cities in the structuring of this trade and the cross border networks. The populating movement and economic opportunities explain the border urbanization. The daily mobility, product flows, networks and economic circuits between the urban and rural markets and between big cities and states reinforce the role of the transit area and its market function. The text goes further by considering that these cross-border practices describe a regionalization approach in which the border make the main link. The territorial process is based on a functional space organized by differents places (former and new ; urbain and rural) and links between them. The border is intensely practiced everyday. It is a part of the collective identity of dendi group. This populated and productive area becomes the support of social identity. It tends to be instituted as border territory. But its management is influenced by national and regional transport and migration policies. These dynamics contribue to the polarization of the territory on border cities. Cross border coordination mechanisms are need to develop insititutional policies in order to consider these problematics of territorialization.